American pastoral [videorecording (DVD)] - McGregor, Ewan, 1971-; Connelly, Jennifer; Fanning, Dakota, 1994-; Riegert, Peter, 1947-; Evans, Rupert; Roth, Philip (Lionsgate, 2017)
Seymour 'Swede' Levov, a once-legendary high school athlete, is a successful businessman married to an ex-beauty queen, Dawn. When Swede and Dawn's daughter disappears after being accused of a violent crime, Swede's perfect life is broken forever and he is left to make sense out of the chaos.